PERANAN TANG KIM TENG DALAM PERANG KEMERDEKAAN DI PEKANBARU TAHUN 1945-1950 - Ari Gabriel Sebastian; Bedriati Ibrahim; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Tang Kim Teng is a fighter of Chinese descent. Tang Kim Teng had a role in the independence war in Pekanbaru in 1945-1950 by smuggling weapons from Singapore to Pekanbaru. The purpose of this research is to know Tang Tang Teng biography, To know the role of Tang Kim Teng in the war of independence in Pekanbaru, To know the end of weapon smuggling activities conducted by Tang Kim Teng, To Know the award obtained by Tang Kim Teng from the Government. The method used in this research is qualitative. Data obtained from the interviews are then analyzed in their own language. The location of the research is Pekanbaru City. This research started from the beginning of the title of this researcher submitted until this thesis is completed. Data collection techniques used are observation techniques, documentation techniques, interview techniques and literature study techniques. The results showed that Tang Kim Teng had a role in the independence war in Pekanbaru by smuggling weapons and supplies from Singapore to Pekanbaru and forwarded to Pekanbaru Regiment IV.Keywords: Tang Kim Teng, Independence, Pekanbaru City